The Fgl2/fibroleukin prothrombinase contributes to immunologically mediated thrombosis in experimental and human viral hepatitis - Marsden, Philip A. (American Society for Clinical Investigation, 2003)
Fibrin deposition and thrombosis within the microvasculature is now appreciated to play a pivotal role in the hepatocellular injury observed in experimental and human viral hepatitis. Importantly, the pathways by which fibrin generation is elicited in viral hepatitis may be mechanistically distinct from the classical pathways of coagulation induced by mechanical trauma or bacterial lipopolysaccharide (LPS). In the setting of murine hepatitis virus strain-3 (MHV-3) infection, a member of the Coronaviridae, activated endothelial cells and macrophages express distinct cell-surface procoagulants, including a novel prothrombinase, Fgl2/fibroleukin, which are important for both the initiation and localization of fibrin deposition. To assess the role of Fgl2/fibroleukin in murine viral hepatitis we generated a Fgl2/fibroleukin–deficient mouse. Peritoneal macrophages isolated from Fgl2/fibroleukin(–/–) mice did not generate a procoagulant response when infected with MHV-3. Fibrin deposition and liver necrosis were markedly reduced, and survival was increased in mice infected with MHV-3. To address the relevance of Fgl2/fibroleukin in human chronic viral hepatitis we studied patients with minimal and marked chronic hepatitis B. We detected robust expression of Fgl2/fibroleukin mRNA transcripts and protein in liver tissue isolated from patients with marked chronic hepatitis B. Fibrin deposition was strongly associated with Fgl2/fibroleukin expression. Collectively, these data indicate a critical role for Fgl2/fibroleukin in the pathophysiology of experimental and human viral hepatitis.